2022
DOI: 10.3389/fmed.2021.782837
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Trabecular Bone Score (TBS) in Bone Quality and Fracture Risk Assessment in Patients on Maintenance Dialysis

Abstract: Maintenance dialysis is associated with almost universal changes in bone metabolism collectively known as chronic kidney disease—mineral and bone disorder (CKD-MBD). These are accompanied in various proportions by bone loss and altered bone quality that led to an increased risk of fracture. Osteoporosis, age-related or postmenopausal, a condition that often coexists with CKD, is also a leading cause of fracture. Dual-energy X-ray densitometry (DXA) is the main tool for assessing the bone quantity and bone loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…observed that lower TBS scores were associated with lower eGFR and increased fracture risk in patients with eGFR ≥ 60 ml/min/1.73 m 2 ( 44 ). Nevertheless, the role of TBS in predicting clinical fractures in prospective studies focused on dialysis patients has not yet been demonstrated ( 45 ). However, an association with higher bone turnover and prevalent fractures has recently been evidenced in end-stage CKD and dialysis ( 40 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…observed that lower TBS scores were associated with lower eGFR and increased fracture risk in patients with eGFR ≥ 60 ml/min/1.73 m 2 ( 44 ). Nevertheless, the role of TBS in predicting clinical fractures in prospective studies focused on dialysis patients has not yet been demonstrated ( 45 ). However, an association with higher bone turnover and prevalent fractures has recently been evidenced in end-stage CKD and dialysis ( 40 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, each decrease of 1 SD in lumbar BMD increased the age-adjusted odds ratio for VFs up to 2.0 times (1.4–2.0) while each SD decrease in total-body BMD increased it up to 1.6 times (1.1–1.6) [ 42 ]. Conversely, the TBS (which adds information on the bone trabecular microarchitecture) was not demonstrated to independently predict clinical fractures (or VFs) in prospective studies in patients with CKD who were undergoing haemodialysis [ 68 , 69 ]. However, a lower TBS was found to be significantly associated with previous non-VFs.…”
Section: Epidemiologymentioning
confidence: 99%
“…Over a period of 5 years, the risk for fracture was not different in individuals with eGFR <60 mL/min/1.73 m 2 compared with those with an eGFR > 60 mL/min/1.73 m 2 . The trabecular bone score (TBS) is a DEXA-derived algorithm for the evaluation of bone microarchitecture whose utility in patient with osteoporosis has been largely demonstrated [ 48 , 114 , 115 ]. Studies have shown that TBS may also be useful to measure bone quality in patients with CKD-MBD [ 114 , 116 ].…”
Section: Bone Fracture In Ckdmentioning
confidence: 99%
“…The trabecular bone score (TBS) is a DEXA-derived algorithm for the evaluation of bone microarchitecture whose utility in patient with osteoporosis has been largely demonstrated [ 48 , 114 , 115 ]. Studies have shown that TBS may also be useful to measure bone quality in patients with CKD-MBD [ 114 , 116 ]. Indeed, in CKD patient, TBS was significantly associated with the histologic parameters of trabecular bone volume and trabecular spacing but not with dynamic parameters, suggesting that TBS reflects trabecular microarchitecture and cortical width [ 117 ].…”
Section: Bone Fracture In Ckdmentioning
confidence: 99%